Mengkritisi Program Tanggungjawab Sosial Perusahaan (CSR) di Perusahaan Migas Sumbagsel - Mr Masduki (Program Studi Ilmu Komunikasi, 2009)
Corporate Social Responsibility (CSR) as a form of corporate self-regulation integrated into a business model is still subject to much debate and criticism. Ideally, CSR policy would function as a built-in, self-regulating mechanism whereby business would monitor and ensure their adherence to law, ethical standards, and international norms. In case of mining industry, corporate would embrace responsibility for the impact of their activities on the environment, consumers, employees, communities, stakeholders and all other members of the public sphere. In South Sumatera and Jambi Province, CSR which was implemented through various community development programs is still face many problems such us limitation of fund, skilled staff and conflict resolution based approach. Still there is a need to transform the concept of CSR from corporate charity or corporate philanthropy to corporate citizenship.